2005
DOI: 10.1097/01.mnm.0000169381.99894.2f
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal intraoperative radioisotope sentinel lymph node mapping in non-small-cell lung cancer

Abstract: These results demonstrate the feasibility of this procedure in identifying the first site of potential nodal metastasis of NSCLC. This method may improve the precision of pathological staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Despite this limitation, advances in CLI technology and techniques continue to be made not only for diagnostic imaging but also for image-guided drug delivery and intra-operative guidance [42][43][44][65][66][67][68][69][70]. Currently multi-modal systems exist to detect malignancy though optical and radiometric detection [71][72][73][74]. As technologies and techniques are refined in this research area, it is entirely plausible that radiometric and CLI-enhanced detection have a role in providing intra-operative guidance within the context of neuroepithelia tumor resection.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this limitation, advances in CLI technology and techniques continue to be made not only for diagnostic imaging but also for image-guided drug delivery and intra-operative guidance [42][43][44][65][66][67][68][69][70]. Currently multi-modal systems exist to detect malignancy though optical and radiometric detection [71][72][73][74]. As technologies and techniques are refined in this research area, it is entirely plausible that radiometric and CLI-enhanced detection have a role in providing intra-operative guidance within the context of neuroepithelia tumor resection.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of skip metastases in patients with non-small cell lung cancer (NSCLC) varies: 13% accordingly to Tanaka et al (Tanaka et al, 2004), 15% accordingly to Rzyman et al (Rzyman, 2006), 18% accordingly to Libshitz et al (Libshitz et al, 1986), 21% accordingly to Lardinois et al (Lardinois et al, 2003), and 25% accordingly to Soltesz et al (Soltesz et al, 2005). Other authors found a even higher prevalence of N2 disease without compromise of hilar nodes (28.5-37.8%) (Tateishi et al, 1994;Yoshino et al, 1996;Prenzel et al, 2003;Misthos et al, 2004, Atinkaya et al, 2005.…”
Section: Introductionmentioning
confidence: 92%